2011
DOI: 10.1167/iovs.10-7077
|View full text |Cite
|
Sign up to set email alerts
|

An ENU-Induced Mutation in theMertkGene (Mertknmf12) Leads to a Slow Form of Retinal Degeneration

Abstract: These findings illustrate that a mutation in the Mertk gene leads to a significantly slower progressive retinal degeneration compared with other alleles of Mertk. These results demonstrate that TNF family members play a role in protecting photoreceptors of Mertk(nmf12) homozygotes from cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
(22 reference statements)
3
22
0
Order By: Relevance
“…Our findings are consistent with the slow peripheral retinal degeneration observed in mice with a Mertk missense mutation generated by ENU mutagenesis on a B6 background [ 35 ], and indicate that a widely available line of Mertk knockout mice is hypomorphic for Tyro3 due to reduced expression from a tightly linked Tyro3 129 allele. Thus, both TYRO3 and MERTK likely function to maintain retinal homeostasis in mice by enabling RPE phagocytosis of POS tips, and the conclusion that MERTK plays a predominant role in the process [ 27 ] should be revised.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with the slow peripheral retinal degeneration observed in mice with a Mertk missense mutation generated by ENU mutagenesis on a B6 background [ 35 ], and indicate that a widely available line of Mertk knockout mice is hypomorphic for Tyro3 due to reduced expression from a tightly linked Tyro3 129 allele. Thus, both TYRO3 and MERTK likely function to maintain retinal homeostasis in mice by enabling RPE phagocytosis of POS tips, and the conclusion that MERTK plays a predominant role in the process [ 27 ] should be revised.…”
Section: Discussionsupporting
confidence: 88%
“…Both strains were mapped to Chr. 12 in F2 intercrosses 26,27 and each allele was backcrossed to C57BL/6J for at least ten generations to eliminate unlinked and distantly linked ENU-induced mutations as potential genetic confounds. A positive allelism test between Nemf R86S and Nemf R487G confirmed that the ENU-induced mutations were disease-causing and were not the result of an unknown, but tightly-linked alternate ENU mutation.…”
Section: Methodsmentioning
confidence: 99%
“…12: 65486719-70085250 bp, GRCm38) and the only exonic variant detected among 15 candidate genes analyzed was in the Nemf gene. The B6J- Nemf R487G line (JAX Stock #18870) was derived from an independent ENU mutagenesis screen for eye phenotypes in a C57BL/6J background, also at The Jackson Laboratory 27 . Crossing heterozygous animals from each ENU allele produced affected offspring in an allelism test suggesting the two mutations were in the same gene.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with Mertk and Tyro3, Axl was the most consistently and strongly induced TAM receptor in macrophages and epithelial cells during primary viral infection, fungal asthma, and viral exacerbation of fungal asthma. Although several individual and combination TAM receptor gene-targeted mice strains are available, all of these adult mice exhibit major immune anomalies that precluded their use in the models used herein (15, 45, 46). Instead, we used mAbs directed against either Axl (42) or Mertk (47) to address the endogenous role of individual TAM receptors in WT mice.…”
Section: Discussionmentioning
confidence: 99%